Synthesis of Core-Shell Fe3O4/C18/SiO2/[3 (2-Aminoethyl amino) propyl] Trimethoxy Silane and The Study of The Adsorption Kinetics Model of Cu2+ and Cr6+ Ions - Mighfar Syukur; Ahmad Fuad Masduqi (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Synthesis of Core-Shell Fe3O4/C18/SiO2/[3 (2-Aminoetil amino) propyl] Trimethoxy silane has been conducted to study its adsorption kinetics of Cu2+ and Cr6+ ions. Fe3O4 synthesis was carried out to form cores that have magnetic properties. The aim of the coating C18/SiO2/[3(2-Aminoetilamino) propyl] trimethoxy silane was to protect these cores from physical degradation due to acids and bases, as well as the application of synthetic materials. The sono-coprecipitation method showed good results under N2 gas flow with the results of black crystals. The success of SiO2 and [3(2-Aminoethylamino) propyl coatings the transformation of the color showed Trimethoxy silane into brown and weight gain of the synthesis result. Analysis of XRD data showed that little Fe2O3 impurities were clarified by FTIR data showing the presence of amine groups from the starting material. The SEM-EDX and TEM showed a spherical shape with a core-shell system. The adsorption kinetics model was studied using two kinetics models for Cu2+ and Cr6+ ions. The results were demonstrated by the suitability of Cu adsorption to the pseudo order 1, with an adsorption rate of 0.0333 min-1, whereas for Cr corresponded to pseudo order 2 with an adsorption rate of 0.00536 gmM-1min-1.